2010
DOI: 10.1093/ejo/cjq059
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic evaluation of profile incisor inclination

Abstract: The objectives of this study were to evaluate (1) the impact of maxillary incisor inclination on the aesthetics of the profile view of a smile, (2) to determine the most aesthetic inclination in the profile view of a smile and correlate it with facial features, and (3) to determine if dentists, orthodontists, and laypeople appreciate differently incisor inclination in smile aesthetics. A smiling profile photograph of a female subject (22 years of age) who fulfilled the criteria of soft tissue normative values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 25 publications
3
31
0
3
Order By: Relevance
“…Recently, Ghaleband Cao et al [2,6] observed that excessively labially or lingually tipped maxillary incisors can significantly worsen the smile esthetics, and that maxillary incisors measurements slightly above the cephalometric standards were preferred for optimum smile esthetics. Thus, lingually tipped maxillary incisors have great potential to significantly compromise not only the occlusal results, but also the smile and facial esthetics [2]. Because of this, the orthodontic mechanics should be highly effective to avoid torque loss of the anterior teeth during Class II malocclusion correction, regardless if treatment is performed with or without extractions.…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Ghaleband Cao et al [2,6] observed that excessively labially or lingually tipped maxillary incisors can significantly worsen the smile esthetics, and that maxillary incisors measurements slightly above the cephalometric standards were preferred for optimum smile esthetics. Thus, lingually tipped maxillary incisors have great potential to significantly compromise not only the occlusal results, but also the smile and facial esthetics [2]. Because of this, the orthodontic mechanics should be highly effective to avoid torque loss of the anterior teeth during Class II malocclusion correction, regardless if treatment is performed with or without extractions.…”
Section: 2mentioning
confidence: 99%
“…The degree of labiolingual inclination of the maxillary and mandibular incisors influences the posterior occlusion, the smile and the facial esthetics [1][2][3][4][5][6]. Improperly inclined incisors may result in all maxillary contact points being located either too mesially or too distally, thus leading to an improper occlusion [3,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Este método se utilizó para cuantifi car las emociones sobre el impacto estético de la inclinación del incisivo central superior en la sonrisa, siendo una herramienta utilizada en varias investigaciones debido a su simplicidad, evitando el sesgo hacia valores preferidos que se encuentran con escalas numéricas o de intervalo, permitiendo un mejor análisis de la cantidad y permitiendo examinar mejor la importancia de las diferencias en las distribuciones (2,14,15). En el presente estudio se realizó una valoración cuantitativa donde se encontraron que la percepción en pacientes presentó un valor de 7,17 cm ± 1,56 cm; mientras que en los estudiantes se obtuvo una valoración 6,74 cm ± 1,32.…”
Section: Discussionunclassified
“…[27][28][29] Dudakların istirahat konumunda olmasıyla, sert ve yumuşak dokular arasındaki ilişkinin yanlış kas aktivasyonu ile kompanse olması önlenmektedir. 22 Bizim çalışmamızda sefalogramların alınması sırasında dudakların ve başın istirahat konumunda olmasına dikkat edildi.…”
unclassified